PRACTICAL ASPACT OF FORMATION OF FOREIGN PROFESSIONAL-COMMUNICATIVE COMPETENCE OF BACHELOR OF AVIONICS IN CONDITIONS OF PROFESSIONAL TRAINING - Глушаниця, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article investigates the practical aspects of formation of foreign professional communicative competence of future specialists in avionics in terms of professional training. The importance of knowledge and skills of professional communication in a foreign language environment for future specialists in avionics has been proved. The necessity of combining theoretical and practical components in the formation of their professional knowledge and skills has been emphasized. The structure of foreign professional communicative competence of Bachelor of avionics has been offered. Based on the communicative approach, the system of exercises and tasks that are focused on the formation of the constituents of the structure of foreign professional communicative competence has been developed